Challenges and coping strategies of indigenous (Aeta) college students in conversational English - Cailvin D. Reyes; Myla L. Isip; Dennis V. Dizon (Northern Negros State College of Science and Technology (NONESCOST), 2021)
English has been regarded as one of the most useful languages in the Philippines yet many Filipino students still face challenges in using the language including the Aeta college students. In this study, the researchers described the Aeta college students' challenges and coping strategies in conversational English. The researchers utilized a qualitative-phenomenological research design in this study. They used a validated interview guide to capture the needed data from the Aeta college students. The researchers adhered to purposive sampling in selecting the participants. After the semi-structured interview, the researchers analyzed the data through a thematic analysis. The findings revealed that indigenous students' conversational English challenges include their belief that they have weaknesses in the English language, such as having a poor vocabulary of the language. Their challenges also include their doubts and lack of confidence, They cope with their challenges by researching and watching people on television. They also consult the dictionary. The proposed module to be used by the indigenous students includes grammar, writing, reading, and vocabulary. The researchers recommend that English instructors and professors should use conversational English as an activity in their classes. Also, they should provide more activities to the students where they can improve their speaking skills, confidence, vocabulary, and understanding of English.